PATIENT WITH CHRONIC HEART FAILURE. RATIONAL CHOICE OF THERAPY - O. M. Drapkina; D. U. Akasheva (Рациональная фармакотерапия в кардиологии)
The theory of chronic hyperactivation of neurohormonal systems, in particular, sympathoadrenal and renin-angiotensin-aldosterone, is the basis of modern concepts of the pathogenesis of heart failure. The medicinal blocking of these two systems has proved to be effective in the treatment of heart failure with reduced ejection fraction (<40%). Antagonists of mineralocorticoid receptors, along with angiotensin-converting enzyme inhibitors and beta-blockers, are neurohumoral modulators. They are used to treat patients with heart failure with reduced ejection fraction. The prescription of mineralocorticoid receptor antagonists in clinical practice remains insufficient despite their high efficacy. Demonstration of the site of mineralocorticoid receptor antagonists in the complex treatment of a patient with chronic heart failure and diabetes type 2 is the goal of this article.